ON THE HISTORY OF CUSTOMS AGENCIES AND POLICE INTERACTION IN TACKLING SMUGGLING IN THE FAR EAST OF RUSSIA - S. N. Lyapustin (Гуманитарные и юридические исследования)
The article discusses the history of interaction between customs authorities and the police in tackling smuggling. Special attention is paid to the practice of bringing police to work together at the customs border and the customs supervision in border cities of the Far Eastern Republic. The article touches upon the issues of interaction including using the capabilities of the intelligence apparatus in the fight against biological resources smuggling. The author refers to the documents in the State archive of the Russian Federation and the Russian state historical archive of the Far East.